7(−3) − 4(5 − 8)/3(−9 + 2)

asked by guest
on Jan 28, 2025 at 1:51 pm



You asked:

Evaluate the expression: 734(58)3(9+2)7 \cdot -3 - \frac{4 \left(5 - 8\right)}{3 \left(-9 + 2\right)}

MathBot Answer:

734(58)3(9+2)=1517=21.5714287 \cdot -3 - \frac{4 \left(5 - 8\right)}{3 \left(-9 + 2\right)} = - \frac{151}{7} = -21.\overline{571428}


734(58)3(9+2)=734(58)13(9+2)=214(58)13(9+2)=214313(9+2)=2143137=214321=2147=1517\begin{aligned}7 \cdot -3 - \frac{4 \left(5 - 8\right)}{3 \left(-9 + 2\right)}& = 7 \cdot -3 - 4 \cdot \left(5 - 8\right) \cdot \frac{1}{3 \cdot \left(-9 + 2\right)}\\& = -21 - 4 \cdot \left(5 - 8\right) \cdot \frac{1}{3 \cdot \left(-9 + 2\right)}\\& = -21 - 4 \cdot -3 \cdot \frac{1}{3 \cdot \left(-9 + 2\right)}\\& = -21 - 4 \cdot -3 \cdot \frac{1}{3 \cdot -7}\\& = -21 - 4 \cdot \frac{-3}{-21}\\& = -21 - \frac{4}{7}\\& = - \frac{151}{7}\end{aligned}